From real to virtual: nature tourism insights. Issue 2 (4th May 2019) - Karadimitriou, Christina
ABSTRACT: There is a fruitful ground for technologies such as augmented and virtual reality to be adopted by the service industry in order to further develop and enhance the unique experience of consumers. The tourism industry (with special reference to nature tourism) is one of the sectors that can very well evolve such technologies in their products and services. Such adoption will increase the engagement towards the destinations and the enterprises. In parallel such technologies can further increase the competitiveness and product and service quality. However, despite the substantial amount of beneficial impacts of such technological adoption, there is a lack of applications specialised in nature tourism. This article provides specific examples and practices suggesting the application of Virtual and Augmented Realities to nature tourism. The study also progresses to the provision of conceptual evidence in order to empower the extended technologies to nature tourism, whilst reducing the hesitance of technological adaptation.